(x+√3)²-10=x²-(√3+2)². Rezolvarea, nu raspunsul.
Răspunsuri la întrebare
Răspuns de
2
(x+√3)²-10=x²-(√3+2)²⇒x²+2x√3+3-10=x²-3-4√3-4⇒x²+2x√3-7=x²-7-4√3⇒2x√3=-4√3⇒x=(-4√3)/(2√3)⇒x=-2
antoniadobrica:
multumesc!
Răspuns de
0
(x+√3)²-10=x²-(√3+2)²
(a+b)²=a²+2ab+b²=>
x²+2x√3+3-10=x²-(3+4√3+4)
x²+2x√3+3-10=x²-3-4√3-4
x²+2x√3+3-10=x²-7√3-4
x²+2x√3-7=x²-7-4√3
2x√3= - 4√3
x= - 4√3
2√3
=>x= - 2
(a+b)²=a²+2ab+b²=>
x²+2x√3+3-10=x²-(3+4√3+4)
x²+2x√3+3-10=x²-3-4√3-4
x²+2x√3+3-10=x²-7√3-4
x²+2x√3-7=x²-7-4√3
2x√3= - 4√3
x= - 4√3
2√3
=>x= - 2
Alte întrebări interesante
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă